Peroxisome proliferator-activated receptor γ agonism attenuates endotoxaemia-induced muscle protein loss and lactate accumulation in rats - Crossland, Hannah; Constantin-Teodosiu, Dumitru; Gardiner, Sheila M.; Greenhaff, Paul L. (Portland Press, 2017)
The peroxisome proliferator-activated receptor γ (PPARγ) agonist rosiglitazone (Rosi) appears to provide protection against organ dysfunction during endotoxaemia. We examined the potential benefits of Rosi on skeletal muscle protein maintenance and carbohydrate metabolism during lipopolysaccharide (LPS)-induced endotoxaemia. Sprague-Dawley rats were fed either standard chow (control) or standard chow containing Rosi (8.5±0.1 mg.kg-1.day-1) for two weeks before and during 24 h continuous intravenous infusion of LPS (15 μg.kg-1.h-1) or saline. Rosi blunted LPS-induced increases in muscle tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) mRNA by 70% (P<0.05) and 64% (P<0.01), respectively. Furthermore, Rosi suppressed the LPS-induced reduction in phosphorylated AKT and phosphorylated Forkhead box O (FOXO) 1 protein, as well as the upregulation of muscle RING finger 1 (MuRF1; P<0.01) mRNA, and the LPS-induced increase in 20S proteasome activity (P<0.05). Accordingly, LPS reduced the muscle protein:DNA ratio (~30%, P<0.001), which Rosi offset. Increased muscle pyruvate dehydrogenase kinase 4 (PDK4) mRNA (P<0.001) and muscle lactate accumulation (P<0.001) during endotoxaemia were suppressed by Rosi. Thus, pre-treatment with Rosi reduced muscle cytokine accumulation and blunted muscle protein loss and lactate accumulation during endotoxaemia, and at least in part by reducing activation of molecular events known to increase muscle protein breakdown and mitochondrial pyruvate use.